2019
DOI: 10.4014/jmb.1904.04065
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antimicrobial Applications of Chitosan Nanoparticles (ChNP)

Abstract: Polymeric nanoparticles are widely used for drug delivery due to their biodegradability property. Among the wide array of polymers, chitosan has received growing interest among researchers. It was widely used as a vehicle in polymeric nanoparticles for drug targeting. This review explored the current research on the antimicrobial activity of chitosan nanoparticles (ChNP) and the impact on the clinical applications. The antimicrobial activities of ChNP were widely reported against bacteria, fungi, yeasts and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…Several parameters control the size of NPs and consequently affect The smaller size of NPs has manifested a significant change in its physical properties compared to its original counterpart. CS-NPs share features of CS and valuable assets of NPs such as small size, increased surface area, and quantum size effects [10][11][12][13][14]. CS-NPs were produced by several procedures such as ionic gelation [41], reverse micellar method [42], microemulsion [43], emulsion droplet coalescence [19], and spray drying [44].…”
Section: Chitosan Nanoparticles (Cs-nps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several parameters control the size of NPs and consequently affect The smaller size of NPs has manifested a significant change in its physical properties compared to its original counterpart. CS-NPs share features of CS and valuable assets of NPs such as small size, increased surface area, and quantum size effects [10][11][12][13][14]. CS-NPs were produced by several procedures such as ionic gelation [41], reverse micellar method [42], microemulsion [43], emulsion droplet coalescence [19], and spray drying [44].…”
Section: Chitosan Nanoparticles (Cs-nps)mentioning
confidence: 99%
“…Among incredible developments in biological technologies and chemical identification methods, nanotechnology has started to play an increasingly important role as it expands the ability to extend antibacterial studies to the atomic level [2]. Chitosan nanoparticles (CS-NPs) are a derivative of CS with excellent physicochemical properties [10][11][12][13][14]. CS-NPs have been prepared by several approaches, such as ionotropic gelation, microemulsion, emulsification solvent diffusion, polyelectrolyte complex and reverse micellar method [12].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(lactic-co-glycolic acid) (PLGA) is one of the most successfully developed biodegradable polymers with good biocompatibility and low toxicity, which has been designed for use in implants, scaffolds, and nanoparticles (NPs) (Almería et al, 2010;Żywicka et al, 2017). Furthermore, chitosan (CTS), a natural polycationic linear polysaccharide with outstanding biocompatibility and antibacterial action, has been considered as a promising nanomaterial (Rozman et al, 2019). Hence, various biomedical and pharmaceutical CTS-based microns or NPs have been developed to enhance the therapeutic effect and reduce irritant or allergic reactions (Diebold, 2010;Gonçalves, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Glinert and coworkers tested a protective antigen based vaccine and found that it was effective against subcutaneous spore challenge but the effi cacy was limited for systemic challenges like intravenous application of virulent strains or mutants with defi cient anthrax toxin (65). Therapies of infectious diseases can be further improved by nanoparticles serving like drug carriers, supporting material for antigen presentation during vaccination or material releasing antibiotics for a wider time span (69)(70)(71)(72)(73)(74)(75)(76). Though there are no relevant studies on anthrax, the applicability of nanoparticles in the therapy can be inferred for the future.…”
Section: Anthrax Therapymentioning
confidence: 99%